Multimodal Biomarkers Quantify Recovery in Autoimmune Autonomic Ganglionopathy. Issue 4 (1st February 2021) - Koay, Shiwen; Vichayanrat, Ekawat; Bremner, Fion; Panicker, Jalesh N.; Lang, Bethan; Lunn, Michael P.; Watson, Laura; Ingle, Gordon T.; Hagen, Ellen Merete; McNamara, Patricia; Jacobson, Leslie; Provitera, Vincenzo; et al.
Abstract : Objective: The objective of this study was to evaluate patients with ganglionic acetylcholine receptor antibody (gAChR‐Ab) positive autoimmune autonomic ganglionopathy using a multimodal testing protocol to characterize their full clinical phenotype and explore biomarkers to quantify immunotherapy response. Methods: We conducted a cohort study of 13 individuals (7 women, 21–69 years of age) with autonomic failure and gAChR‐Ab >100 pM identified between 2005 and 2019. From 2018, all patients were longitudinally assessed with cardiovascular, pupillary, urinary, sudomotor, lacrimal and salivary testing, and Composite Autonomic Symptom Score (COMPASS‐31) autonomic symptom questionnaires. The orthostatic intolerance ratio was calculated by dividing change in systolic blood pressure over time tolerated on head‐up tilt. Eleven patients received immunotherapy. Results: At first assessment, all 13 patients had cardiovascular and pupillary impairments, 7 of 8 had postganglionic sudomotor dysfunction, 9 of 11 had urinary retention and xeropthalmia, and 6 of 8 had xerostomia. After immunotherapy, there were significant improvements in orthostatic intolerance ratio (33.3 [17.8–61.3] to 5.2 [1.4–8.2], p = 0.007), heart rate response to deep breathing (1.5 [0.0–3.3] to 4.5 [3.0–6.3], p = 0.02), pupillary constriction to light (12.0 [5.5–18.0] to 19.0 [10.6–23.8]%, p = 0.02), saliva production (0.01 [0.01–0.05] to 0.08 [0.02–0.20] g/min, p = 0.03), and COMPASS‐31 scores (52 to 17, p = 0.03). Orthostatic intolerance ratio correlated with autonomic symptoms at baseline (r = 0.841, p = 0.01) and following immunotherapy (r = 0.889, p = 0.02). Immunofluorescence analyses of skin samples from a patient 32 years after disease onset showed loss of nerve fibers supplying the dermal autonomic adnexa and epidermis, with clear improvements following immunotherapy. Interpretation: Patients with autoimmune autonomic ganglionopathy demonstrated objective evidence of widespread sympathetic and parasympathetic autonomic failure, with significant improvements after immunotherapy. Quantitative autonomic biomarkers should be used to define initial deficits, guide therapeutic decisions, and document treatment response. ANN NEUROL 2021;89:753–768